El filicidio. Algunos recaudos conceptuales - Kalinsky, Beatriz (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
In this paper we intend to discern the epistemological foundations and the social performance of two concepts that are being, at the present time, bound to violence situations: "filicide" and "syndrome of the battered woman". A deconstruction of both concepts is tried using data of a fieldwork made in the Province of the Neuquén (Argentina), pertinent scientific Literature and the application of both concepts in the judicial defences and sentences. We considered that both concepts do not have to be considered in causal form. The concept of "syndrome of the battered woman" does not give account of the phenomenon of filicide; although they can be associate in particular circumstances given the public extension that has acquired the violence exerted against women. The main argumentation is that the concept of "syndrome of the battered woman" leaves intact the prevailing stereotype of a "good- bad mother". Filicide as social phenomenon should have to be treated in independent form. The filicidal conduct has adjudged a set of hypotheses that try to report their genesis and outbreak, between which appears the conjugal violence. But this one by itself cannot give account of the totality of the meaning by which a mother can exert damage or lethal violence against her children.